KIF21A pathogenic variants cause congenital fibrosis of extraocular muscles type 3. (4th March 2021) - Al-Haddad, Christiane; Boustany, Rose-Mary; Rachid, Elza; Ismail, Karine; Barry, Brenda; Chan, Wai-Man; Engle, Elizabeth
ABSTRACT: Background: Congenital fibrosis of the extraocular muscles (CFEOM) is characterized by ptosis and non-progressive restrictive ophthalmoplegia. CFEOM1 is a stereotypical phenotype with isolated bilateral ptosis, bilateral ophthalmoplegia, absent upgaze, and globe infraduction. CFEOM3 is a more variable phenotype that can include unilateral disease, absent ptosis, residual upgaze, and/or orthotropia. Most cases of CFEOM1 result from recurrent heterozygous KIF21A missense mutations and less commonly from recurrent heterozygous TUBB3 missense mutations. While most cases of CFEOM3 result from recurrent heterozygous TUBB3 missense mutations, several pedigrees harbored pathogenic variants in KIF21A . Here, we asked if Lebanese pedigrees with CFEOM3 harbor pathogenic variants in TUBB3 or KIF21A. Materials and Methods: Families affected with congenital cranial dysinnervation disorders were prospectively recruited from the American University of Beirut pediatric ophthalmology clinic and included two probands with CFEOM. KIF21A hotspot exons and TUBB3 coding sequence were sequenced. Available family members were sequenced for co-segregation analysis. Results: Both families were found to have CFEOM3 and to harbor pathogenic variants in KIF21A (OMIM 608283). A simplex proband with CFEOM3 from a consanguineous Iraqi family harbored a de novo heterozygous KIF21A c.2860 C > T variant (p.R954W); this variant accounts for the majority of reported KIF21A mutations but is typically implicated in CFEOM1. A Lebanese father with CFEOM3 and his son with CFEOM1 segregated a heterozygous KIF21A c.2830 G > C variant (p.E944Q), previously reported in an individual with CFEOM1. Conclusions: These results support prior reports of KIF21A mutations as a rare cause of CFEOM3. These families are Middle Eastern or Chinese, supporting a genetic modifier in these populations.